The carnivalesque and event evolution: a study of the Beltane Fire Festival. Issue 1 (2nd January 2016) - Matheson, Catherine M.; Tinsley, Ross
Abstract : This paper centres on the Beltane Fire Festival in Edinburgh, Scotland. The objectives are to: first, identify the stages of the festival's evolution and their respective characteristics; second, distinguish features corresponding to the carnivalesque; and, finally, examine the changes in event evolution, particularly regulatory interventions, and their effect. A qualitative approach comprising interviews with internal and external festival stakeholders was utilised. It is argued that there are three stages in the festival's evolution: revival and early development; development and regulation; and, maturation. The characteristics of these evolutionary stages are identified. As the festival has developed and been subject to increasing regulation, features of the carnivalesque have been reduced.